The decrease of depolarization temperature and the improvement of pyroelectric properties by doping Ta in lead-free 0.94Na0.5Bi0.5TiO3-0.06BaTiO3 ceramics - Balakt, Ahmed M.; Shaw, Christopher P.; Zhang, Qi (Elsevier, 2016)
Ta-doped lead-free 0.94NBT-0.06BT-xTa (x=0.0–1.0%) ceramics were synthesized by a conventional solid-state route. XRD shows that the compositions are at a morphotropic phase boundary where rhombohedral and tetragonal phases coexist. The depolarization temperature (Td) shifted to lower temperature with the increase of Ta content. The pyroelectric coefficient (p) of doped ceramics greatly enhanced compared with undoped material and reached a maximum of 7.14×10−4 C m−2 °C−1 at room temperature (RT) and 146.1×10−4 C m−2 °C−1 at Td at x=0.2%. The figure of merits, Fi and Fv, also showed a great improvement from 1.12×10−10 m v−1 and 0.021 m2 C−1 at x=0.0 to 2.55×10−10 m v−1 and 0.033 m2 C−1 at x=0.2% at RT. Furthermore, Fi and Fv show the huge improvement to 52.2×10−10 m v−1 and 0.48×10−10 m v−1 respectively at Td at x=0.2%. FC shows a value between 2.26 and 2.42 ×10−9 C cm−2 °C−1 at RT at x=0.2%. The improved pyroelectric properties make NBT-0.06BT-0.002Ta ceramics a promising infrared detector material.
Keywords: Lead free ceramics; Lanthanum doping NBT-BT; Morphotropic phase boundary (MPB); Depolarization temperature; Pyroelectric properties; Figure of merits